Synthesis and characterisation of organotin (IV) carboxylate complexes / Kelly Tan Ching Yi - Tan, Kelly Ching Yi (2014)
Two organotin (IV) carboxylate complexes were prepared by the refluxed synthesized in ethanol and acetonitrile respectively. Both reactions are carried out with organotin (IV) complexes and carboxylic acid in 1:1 stoichiometric reaction. The water molecules formed during the reaction is removed from the mixture by molecule sieve and a Dean and Stark apparatus. Complexes have been characterized by elemental analysis, melting point determination, Fourier Transform Infrared spectroscopy and multinuclear Magnetic Resonance (1H, 13C and 119Sn) studies were carried out to elucidate their structures. The differences [υ(COO)], where [υ(COO)as -[υ(COO)s] was determined indicating complex 1 is bidentate with ligand while complex 2 forms a monodentate with ligand. 119Sn NMR is important in determining the coordination number of tin atom moiety of the complexes obtained. The structure complex 1 shows the Sn atom is five-coordinated and six-coordinated with the coordination sphere is distorted trigonal bipyramid and octahedral. While for the molecular structure of compound 2, the tin atom is four-coordinated in a slightly tetrahedral geometry